Changes in Routine Blood Tests in COVID-19: A Case at Janaki Medical College (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: COVID-19 is an infectious disease caused by the SARSCoV-2 virus, which has resulted in a worldwide media attention and public alarm. COVID-19 has a wide variety of clinical features, ranging from asymptomatic infection to mild to severe pneumonia. Different laboratory parameters get altered in COVID-19 patients. Therefore, biochemical investigations are important to assess the progression of the disease and categorize patients that may present a severe and/or fatal clinical condition.CASE PRESENTATION: The present case shows a 56-year-old male, without any significant medical history or comorbidities, suddenly developed fever and shortness of breath returning home attending a marriage ceremony at his village. He had the history of traveling but unaware about COVID-19 prone areas or with a direct contact of COVID-19 positive patients. The patient was primarily treated with medicines at home on telephonic consultation by physician but, didn’t recover. During hospitalisation, his chest X-ray revealed ground-glass opacity in the right middle and lower zone of the lung. He was tested RT-PCR positive after X-ray.CONCLUSIONS: This case study concludes with lower levels of WBCs, Hb, lymphocytes, and eosinophils. The liver function tests were altered as well as renal impairment was common. The patient was encouraged to maintain home quarantine for at least 14 days after treatment. COVID-19 patient’s prognosis may be improved by monitoring haematological and biochemical changes.